ANALISIS CAR, NPL, BOPO, NIM, LDR DAN PENGARUHNYA TERHADAP PROFITABILITAS PADA BANK ARTHA GRAHA INTERNASIONAL TBK - I Ketut Wenten (LPPM Universitas Putera Batam, 2018)
The purpose of this study is to analyze and know the conclusions about the effect of the above variables on Profitability at Bank Artha Graha International proxy with Return on Assets (ROA). Data used in this study quarterly Financial Report period March 2001 - December 2014 based on the publication of Indonesian Banking Directory listed on the Financial Services Authority (OJK) and Bank Indonesia (BI) and the profile of the company Bank Artha Graha International Tbk. The research method used is analytical associative analytical analytical, analytical analytical research that aims to know the relationship between two or more variables, the method of explaining, predict and control a symptom. while the analytical causal associative is the causal relationship where the variable X will affect the variable Y. while the analytical technique used is multiple linear regression with quadratic equations and hypothesis test by using t-statistics for partially and F-statistics for the simultaneous. From partial research result; The effect of CAR on ROA of t count <t-table (-2,626 <-2.008) and probability 0.0114 <0.05 then H01 rejected, NPL effect on ROA t count> t-table (-1,7638> -2,008 ) with probability 0.08> 0.05 then H02 received, the effect of BOPO on the ROA of t count <t-table (-3,9819 <-2.008) and probability 0.0002 <0.05 then rejected, the effect of NIM on ROA the result of t arithmetic> t-table (5,115> 2,008) and probability 0.000 <0,05 then H04 rejected, influence of LDR to ROA t count <t-table (1,292 <2,008) and probability 0,202> 0, 05 then H05 accepted. The result of F test (simultaneously) shows F count> F-table or 63,76> 2,008 with probability value (significance) 0,000 <0,05. Can have a significant effect on the dependent variable ROA, BOPO independent variable there is a significant negative effect on the dependent variable ROA and NIM variable no significant positive effect on the ROA variable. NPL and LDR variables partially have no significant effect on ROA dependent variable at probability level (significance) less than 5%. The influence of variable variables (CAR, NPL, BOPO, NIM, and LDR) simultaneously significant and significant to profitability (ROA). From the results of this study is expected to be a guide, both by the management company in the management of companies and by investors in determining the investment strategy.